The gut microbiota structure of the terrestrial isopod Porcellionides pruinosus (Isopoda: Oniscidea). Issue 1 (1st January 2020) - Delhoumi, M.; Catania, V.; Zaabar, W.; Tolone, M.; Quatrini, P.; Achouri, M. S.
Abstract: We used a combination of culture-dependent and independent approaches to study in depth the microbial community associated with the digestive tract of the terrestrial isopod Porcellionides pruinosus (Brandt, 1833 ). Specimens from different sampling sites in Tunisia harbored distinct microbiota profiles indicating the impact of both host origin and environmental factors on shaping the microbial flora within P. pruinosus . Our results revealed unexpected bacterial diversity especially via metagenomic analysis; a total of 819 operational taxonomic units (OTUs) assigned to two major bacterial phyla; Proteobacteria and Bacteroidetes . We used Nutrient Agar to isolate the cultivable fraction of bacteria associated with the gut of three geographically distant populations of P. pruinosus . The isolated bacteria belong to Actinobacteria, Firmicutes and Proteobacteria . Enrichment cultures on carboxymethylcellulose (CMC) medium gave evidence that the gut of this Oniscidea harbors cellulolytic Firmicutes and Proteobacteria probably involved in the lignocellulose degradation and then in mediating the functional role of terrestrial isopods as litter decomposers and regulators of nutrient cycling in soil ecosystems.